A STUDY ON RESERVATION POLICY OF CENTRAL GOVERNMENT IN EDUCATION SECTOR - Jeevan Kumar. P, Mrs. K.S. Bala Thirupura Sundari, (International Journal of Advanced Science and Technology, 2020)
Reservation policy of Central Government in the education sector. In India there are several kinds of Reservation Policy Based on Religion,Caste,Income and Backward Community etc. According to the Reservation policy by  The Central Government of India. Indian Higher Educational Institutions 15%and 7.5% for SC And ST Candidates in Educational Policy. The Reservation policy is an integral Part of Indian Educational Institutions over a period of Years. After the Independence of India The students belonging to Backward Communities have been admitted on the basis of quota. The Reservation policy was introduced in India by Ambedkar. The main motive is to help the deprived society and well-being of Backward Communities in India. The Central government has made few changes according to Current Scenario for the Education Sector for Students. Recent Survey on Reservation policy for Educational sector in India Report indicates that 2018-19 Approximately More than Three crore Students were enrolled  in the Indian Higher education last year approximately 55% students were Backward Communities.Education should Determine Knowledgeable students with Highly Intellectual,skills and capacity and there should not be any Political Influences or Interferences in Educational Policy. For the purpose of Non-Doctrinal empirical study research we used descriptive method and Convenient sampling method study on Reservation policy in Education sector in India. Convenient sampling method is used to collect the sample. 1665 sample size.